A novel kinase inhibitor, LZT-106, downregulates Mcl-1 and sensitizes colorectal cancer cells to BH3 mimetic ABT-199 by targeting CDK9 and GSK-3β signaling. (1st February 2021) - Yu, Zhou; Du, Jiaying; Zhao, Yue; Gao, Yuan; Li, Yongxu; Zhao, Kai; Lu, Na
Abstract: Colorectal cancer (CRC) is one of the most common malignancies worldwide and is associated with poor prognosis and high mortality. Despite advances in treatment with chemotherapy, CRC remains a major cause of drug resistance-related cancer deaths. One of the main reasons for such resistance is dysregulation of Mcl-1 expression. In this study, we identified LZT-106 as a novel kinase inhibitor that was able to bind to CDK9 with potent inhibitory ability, and indirectly regulate the expression of Mcl-1. However, different regulatory profiles were observed between LZT-106 and the well-studied CDK9 inhibitor flavopiridol with regards to Mcl-1 inhibition. Via Western blotting, real-time PCR and immunoprecipitation, we confirmed that LZT-106 was also able to target GSK-3β signaling and facilitate the degradation of Mcl-1. And LZT-106 was shown to synergize with ABT-199 to induce apoptosis even in the RKO cell line that overexpressed Mcl-1. Finally, LZT-106 significantly inhibited tumor growth in a xenograft mouse model with minimal toxicity. Overall, our findings suggest that LZT-106 is a promising candidate drug for the treatment of patients with CRC. Graphical abstract: The flowchart of this experiment. This study suggests that LZT-106 promotes decrease of Mcl-1 by dual targeting CDK9 and GSK-3β signaling. Targeting GSK-3β promotes degradation of Mcl-1 in proteasome pathway, which provides another way with LZT-106 to target Mcl-1. So LZT-106 could downregulate Mcl-1 potently and enhance proapoptotic activity of ABT-199 Image 1 Highlights: LZT-106 is a novel kinase inhibitor that downregulates Mcl-1 by dual targeting CDK9 and GSK-3β signaling. Targeting GSK-3β promotes degradation of Mcl-1 in proteasome pathway. LZT-106 might be a candidate drug to enhance therapeutic effect of ABT-199 for the treatment of colorectal cancer.